Psychological and Psychosocial Interventions for Preventing Perinatal Depression in Single Mothers: A Systematic Review and Meta-Analysis - Andrian Fajar Kusumadewi; Khazaini Azmi Nabila; Aftin Istaqroba Saifi Elhaq; Shafira Fitri Fawzia (HM Publisher, 2025)
Introduction: Perinatal depression affects approximately 26.3% of mothers globally. Single mothers face an elevated risk due to financial instability and limited support. While preventive psychological and psychosocial interventions are proven in general populations, their specific efficacy for single mothers remains unclear. This systematic review and meta-analysis evaluate these interventions' effectiveness in preventing perinatal depression in this vulnerable group. Methods: Searching five major databases through September 2025, we identified randomized controlled trials evaluating psychological (cognitive-behavioral therapy) and psychosocial interventions for single mothers from pregnancy through one year postpartum. Nine studies (n=681) met the inclusion criteria, utilizing a 75% single-motherhood threshold. We analyzed depressive symptom severity (Standardized Mean Difference, SMD) and episode incidence (Relative Risk, RR) using a random-effects meta-analysis. Results: The meta-analysis for depressive symptoms (k=5; n=418) demonstrated a significant protective effect (pooled SMD = -0.585; 95% CI: -0.883 to -0.287; p = 0.0001) with minimal heterogeneity. For depressive episodes (k=3; n=171), incidence was reduced by 64% (RR = 0.36; 95% CI: 0.18 to 0.71). Despite these positive outcomes, GRADE assessment yielded a low certainty of evidence due to imprecision and severe geographic bias, as eight of the nine studies were US-based. Conclusion: Psychological and psychosocial interventions can reduce perinatal depressive symptoms and incidence among single mothers. However, given the small evidence base, temporal limitations, and geographic concentration, findings warrant cautious interpretation. Further large-scale, globally diverse trials are essential before widespread clinical implementation can be confidently recommended.